2019
DOI: 10.1155/2019/2673543
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Methylated DNA Biomarkers in Patients with Colorectal Cancer

Abstract: Colorectal cancer (CRC) is a leading cancer globally; therefore, early diagnosis and surveillance of this cancer are of paramount importance. Current methods of CRC diagnosis rely heavily on endoscopy or radiological imaging. Noninvasive tests including serum detection of the carcinoembryonic antigen (CEA) and faecal occult blood testing (FOBT) are associated with low sensitivity and specificity, especially at early stages. DNA methylation biomarkers have recently been found to have higher accuracy in CRC dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 47 publications
3
31
0
Order By: Relevance
“…Experimental evidence for the hypermethylation of the promoter region of LAMA1 in CRC patients is available [53]. NELL1 is a known tumor suppressor gene [54], whose hypermethylation is associated with poor survival outcomes [55]. Our results that NELL1 is a stage IV-specific hypermethylated gene resonates with the above findings.…”
Section: Stage-iv Salient Dmgssupporting
confidence: 82%
“…Experimental evidence for the hypermethylation of the promoter region of LAMA1 in CRC patients is available [53]. NELL1 is a known tumor suppressor gene [54], whose hypermethylation is associated with poor survival outcomes [55]. Our results that NELL1 is a stage IV-specific hypermethylated gene resonates with the above findings.…”
Section: Stage-iv Salient Dmgssupporting
confidence: 82%
“…The sensitivity and specificity of the diagnostic panel consisting of CEA, CA19-9, CA242, CA211, and CA724 were 83% and 95%, respectively, which were similar to those of detection of SEPT9 gene methylation in peripheral blood. The sensitivity and specificity of the most commonly used single serum CEA were lower than those of SEPT9 gene methylation[ 62 - 64 ]. Colonoscopy biopsy combined with pathological diagnosis is the golden standard for the diagnosis of CRC.…”
Section: Sept9 and Colorectal Cancermentioning
confidence: 99%
“…To date, none of these markers have been used in clinical practice. Recently Draht et al [ 190 ] and Ma et al [ 191 ] comprehensively reviewed the published prognostic methylation markers for CRC and marked the most promising ones. Studies focusing on the hypermethylation of the IGFBP3 gene have shown correlations with a poor prognosis in CRC patients [ 175 , 192 , 193 ].…”
Section: Clinical Applications Of Dna Methylation Profilingmentioning
confidence: 99%